Defining and Predicting Early Recurrence in 957 Patients With Resected Pancreatic Ductal Adenocarcinoma. Issue 6 (June 2019) - Groot, Vincent P.; Gemenetzis, Georgios; Blair, Alex B.; Rivero-Soto, Roberto J.; Yu, Jun; Javed, Ammar A.; Burkhart, Richard A.; Rinkes, Inne H. M. Borel; Molenaar, I. Quintus; Cameron, John L.; Weiss, Matthew J.; Wolfgang, Christopher L.; et al.
Abstract : Objectives: To establish an evidence-based cut-off to differentiate between early and late recurrence and to compare clinicopathologic risk factors between the two groups. Summary Background Data: A clear definition of "early recurrence" after pancreatic ductal adenocarcinoma resection is currently lacking. Methods: Patients undergoing pancreatectomy for pancreatic ductal adenocarcinoma between 2000 and 2013 were included. Exclusion criteria were neoadjuvant therapy and incomplete follow-up. A minimum P -value approach was used to evaluate the optimal cut-off value of recurrence-free survival to divide the patients into early and late recurrence cohorts based on subsequent prognosis. Potential risk factors for early recurrence were assessed with logistic regression models. Results: Of 957 included patients, 204 (21.3%) were recurrence-free at last follow-up. The optimal length of recurrence-free survival to distinguish between early (n = 388, 51.5%) and late recurrence (n = 365, 48.5%) was 12 months ( P < 0.001). Patients with early recurrence had 1-, and 2-year post-recurrence survival rates of 20 and 6% compared with 45 and 22% for the late recurrence group (both P < 0.001). Preoperative risk factors for early recurrence included a Charlson age-comorbidity index ≥4 (OR 1.65), tumor size > 3.0 cm on computed tomography (OR 1.53) and CA 19-9 > 210 U/mL (OR 2.30). Postoperative risk factors consisted of poor tumor differentiation grade (OR 1.66), microscopic lymphovascular invasion (OR 1.70), a lymph node ratio > 0.2 (OR 2.49), and CA 19-9 > 37 U/mL (OR 3.38). Adjuvant chemotherapy (OR 0.28) and chemoradiotherapy (OR 0.29) were associated with a reduced likelihood of early recurrence. Conclusion: A recurrence-free interval of 12 months is the optimal threshold for differentiating between early and late recurrence, based on subsequent prognosis.